Membangun Paradigma Baru Ekonomi Islam Untuk Penanggulangan Pengangguran - Dalmeri Dalmeri (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
The economic crisis that hit Indonesia since 1997 is still challenging, while in other Asian countries has shown development which evidenced by the economic recovery in various economic sectors and the increasing in capital income is far better than the Indonesian capital income. Other part of Asian countries has increased their employment while in Indonesia has not yet improved. The catastrophic of Economic Crisis in Indonesia causing many losses, increasing unemployment, increasing the crime. Economists claimed that the capitalist system is suspected to be system which caused the economic crisis. Based on this, Islamic Economic could be as an alternative and hoped to be the answer to tackle the challenges in future world. The article try to analyze new Islamic economic paradigm to tackle the unemployment.